Lah, Uratnik in Bilimovič - začetniki statistične analize na področju družbenoekonomskih raziskav v Sloveniji - Južnič, Stanislav (Teorija in praksa, 2007)
The paper deals with statistical contributions of Ivo Lah, Filip Uratnik and Aleksander Bilimovič in Ljubljana between the wars. In the first section there is a brief review of Russian mathematical and statistical tradition, which had a strong impact on the work of Lah and Bilimovič. Lah and Uratnik dealt with the problems of the social insurance of Slovenian workers. The data on social insurance were used by Lah and Bilimovič to analyse the business fluctuations of the Slovenian economy. Lah and Bilimovič wrote also on statistical theory and Lah on problems in insurance mathematics. Uratnik was interested in demographic and social statistics; he carried out some pioneering research about the living standards of the Slovenian population. The published works of Lah, Uratnik and Bilimovič reveal their mutual interest in the statistical analysis of the socio-economic issues of the time.
Keywords: Lah, Ivo, 1896-1979; Statistics; Uratnik, Filip, 1889-1967; Statistical methods; Social insurance; Bilimovič, Aleksander, 1876-1963; Demography; Statistika; Statistične metode; Economic history; Socialno zavarovanje; Socioeconomic development; Demografija; Researchers; Ekonomska zgodovina; Cooperation; Družbenoekonomski razvoj; Slovenia; Raziskovalci; Sodelovanje; Slovenija